Exploring the interrelationships between critical thinking, practical skills, and summative achievement in secondary biotechnology education - Nurhayati Nurhayati; Lilit Rusyati; Nuryani Y. Rustaman; Rizky Agassy Sihombing (Education and Development Research, 2026)
Modern science education faces a persistent challenge: the disconnect between theoretical critical thinking development and hands-on practical competencies. This study investigated the relationships among critical thinking skills, practical performance, and summative achievement in ninth-grade biotechnology education within Indonesia's Merdeka Curriculum framework, which emphasizes conceptual understanding, scientific process skills, and 21st-century competencies. The research objective was to examine whether and how critical thinking abilities and practical performance independently or jointly predict summative academic achievement in biotechnology. Using a correlational design, data were collected from 113 ninth-grade students across four intact classes at a public junior high school in Bandung, West Java. Three validated assessment instruments measured the target variables: a critical thinking skills test based on Ennis indicators assessing analytical reasoning abilities, a performance rubric evaluating hands-on laboratory proficiency during practical sessions, and a standardized summative biotechnology examination measuring overall content mastery. Descriptive statistics revealed varied performance across assessment types, with mean scores of 59.7 for critical thinking skills, 86.6 for practical performance, and 70.4 for summative achievement. Pearson correlation analyses conducted in SPSS indicated a moderate positive relationship between critical thinking and summative scores, a weak positive association between practical performance and summative achievement, but critically, no significant correlation between critical thinking and practical performance. These findings suggest that while analytical reasoning contributes to theoretical academic success, procedural competencies operate largely independently from cognitive reasoning abilities in biotechnology contexts. The study suggests that science educators should implement integrated teaching methods deliberately bridging practical skills development with explicit critical thinking instruction to foster holistic scientific literacy.